Vallejo from the perspective of teachers - Olórtegui Mariño, Maritza (Espergesia, 2015)
This article closely links Cesar Vallejo’s poetry with educational practice. That is to say, how to promote, encourage and enrich the reading of Vallejo’s universe in our classrooms. To promote -in our students- a critical and evaluative attitude of Vallejo’s poetry, associated with ethical and daily actions of society. Vallejo's poetry suggests hints and worries. This poetic condition establishes the semantic multiplicity of literary discourse. That is, Vallejo's poetry makes an active reader (students) of those who get involved in the textual interpretation.